Making Simple Repairs: Using a Plunger to Unstop a Toilet - Mary N. Harrison (EDIS)
There may be a time when your toilet is stopped up; the water will not drain out. You may be able to unstop it by using a plunger. This document is FCS5234-04, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.